The Effect of the RME-Based Argument-Driven Inquiry (ADI) Learning Model on Mathematical Problem-Solving Skills Regarding Systems of Linear Equations in Three Variables (SPLTV) - Miftah Khairiyah; Reflina Reflina (MASI Mandiri Edukasi, 2026)
Mathematical problem-solving ability is an essential competency in mathematics learning, yet students still experience difficulties in understanding problems, determining strategies, and evaluating solutions. Although Argument-Driven Inquiry (ADI) and Realistic Mathematics Education (RME) have been widely applied in mathematics learning, their integration to improve mathematical problem-solving ability remains relatively limited. Therefore, this study aims to analyze the effect of the RME-based ADI learning model on students' mathematical problem-solving abilities in Systems of Linear Equations in Three Variables (SPLTV). This quantitative study employed a quasi-experimental Pretest-Posttest Control Group Design involving 72 Grade X students at SMA Negeri 2 Percut Sei Tuan. Data were collected using an essay test and analyzed using descriptive statistics, the Shapiro–Wilk test, Levene's test, independent-samples t-test, and Cohen's d. The experimental class obtained a higher mean post-test score (85.24) than the control class (67.56), with p < 0.001 and an effect size of 3.548, categorized as a huge effect. These findings indicate that the RME-based ADI model can be an effective alternative for improving students' mathematical problem-solving abilities.